Teachers, contents and evaluation in the new educational paradigm - Lucía Almazán Ruiz (ADIDE Federación, 2013)
The new educational paradigm proposed by Sir Ken Robinson brings a thorough review of the key factors involved in the processes of teaching and learning. In this article we have tried to highlight three aspects that we consider more sensitive to adapt to the new changes that are occurring in education: the figure of the teacher, as well as learning guide as generator of his own content, content education, considering the digital medium and the use of ICT as more plausible trend, and assessment processes, adjusting them to the skills and educational feedback more than the sum of results or products.